2014
DOI: 10.1088/0029-5515/54/5/054003
|View full text |Cite
|
Sign up to set email alerts
|

Theory of fast electron transport for fast ignition

Abstract: Abstract. Fast Ignition Inertial Confinement Fusion is a variant of inertial fusion in which DT fuel is first compressed to high density and then ignited by a relativistic electron beam generated by a fast (< 20 ps) ultra-intense laser pulse, which is usually brought in to the dense plasma via the inclusion of a re-entrant cone. The transport of this beam from the cone apex into the dense fuel is a critical part of this scheme, as it can strongly influence the overall energetics. Here we review progress in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 216 publications
(596 reference statements)
3
87
0
2
Order By: Relevance
“…In the previous review paper [16], the beam guiding by magnetic-pipe was discussed for the ignition-scale electron beam (the beam energy Eb > 100 kJ, the intensity Ib ~ 10 20 -10 21 W/cm 2 , the pulse duration τb~ 20ps). It was reported that in the case of such high energy beams, the direction of longitudinal B-field affects the guiding performance.…”
Section: F(e)∝ Al Exp(-e/tl) + Ah Exp(-e/th) the Low Energy Componenmentioning
confidence: 99%
“…In the previous review paper [16], the beam guiding by magnetic-pipe was discussed for the ignition-scale electron beam (the beam energy Eb > 100 kJ, the intensity Ib ~ 10 20 -10 21 W/cm 2 , the pulse duration τb~ 20ps). It was reported that in the case of such high energy beams, the direction of longitudinal B-field affects the guiding performance.…”
Section: F(e)∝ Al Exp(-e/tl) + Ah Exp(-e/th) the Low Energy Componenmentioning
confidence: 99%
“…Ultraintense laser-driven REs have attracted great recent attention 1,2 due to their potential application in the areas of fast ignition laser fusion [3][4][5][6] , ion acceleration by laser-plasma interaction 7,8 , and production of ultrashort bright radiations 9 . It is essential to characterize accurately the RE divergence for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical expressions of the collisional operators are obtained from Davies 13 equations (1) and (2). More details about the physics of hybrid code can be found in the study by Robinson et al 8 A 200 Â 100 Â 100 grid was used with a 0.5 lmc e l ls i z e in each direction. The number of macroparticles injected into each of the cells was 126.…”
Section: Simulation Set Upmentioning
confidence: 99%
“…This implies that the product of B / L / needs to be larger than the fast electron momentum to reflect the fast electrons back towards the guide axis. The resistive guide has been suggested for applications such as the Fast Ignition approach to the inertial confinement fusion scheme 6,7 where the energetic fast electrons need to be guided through an overdense stand-off distance of 100 lm or more 8 and deposited into the compressed core of deuterium-tritium (DT) plasma. It has been suggested that a resistive guide element can also be used as a driver in hydrodynamic experiments 4,9 since strong heating occurs where the fast electron beam is collimated.…”
Section: Introductionmentioning
confidence: 99%